Pengembangan Inovasi Kemasan Produk UMKM Tarekli Khas Salama Kota Bima - Ita Purnama; Nurkaidah Putri; Juhana Safitri (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
The COVID-19 pandemic has driven many businesses to innovate, particularly in product branding and packaging to remain competitive in the digital era. This community service project aimed to empower local SMEs in Salama, Kota Bima, with a focus on the traditional snack "Tarekli", which lacked attractive packaging and product variation. The objectives of the program were to increase product appeal and marketability through innovative packaging design and flavor development. The methods used included direct observation, surveys, and interviews with local Tarekli producers. The program was carried out in three stages: preparation, implementation, and evaluation. During the preparation stage, suitable packaging themes and flavor concepts were discussed. In the implementation phase, customized packaging was designed collaboratively with the SMEs, considering cost, aesthetics, and practicality. The evaluation stage involved revisiting the SMEs to assess the effectiveness and sustainability of the new product packaging and variations. The results indicated increased customer interest and a positive response from local markets, showing that aesthetic packaging and diverse flavors significantly enhance the competitiveness of traditional products. This project highlights the importance of packaging innovation and product development as strategic tools in supporting local economic empowerment.